Equal Representation Does Not Mean Equal Opportunity: Women Academics Perceive a Thicker Glass Ceiling in Social and Behavioral Fields Than in the Natural Sciences and Economics - van Veelen, Ruth; Derks, Belle (Frontiers in Psychology, 2022)
In the study of women in academia, the focus is often particularly on women's stark underrepresentation in the math-intensive fields of natural sciences, technology and economics (NTE). In the non-math-intensive of fields life, social and behavioral (LSB) sciences, gender issues are seemingly less at stake because, on average, women are well-represented. However, in the current study we demonstrate that equal gender representation in LSB disciplines does not guarantee women's equal opportunity to advance to full professorship - to the contrary. With a cross-sectional survey among N=2109 academics at midlevel careers (i.e., assistant and associate professors) in the Netherlands, we test the hypothesis that in LSB (more than NTE), female academics perceive to hit a 'thicker' glass ceiling - that is, they see a sharper contrast between the high representation of women at the lower compared to the top levels. We test whether this predicts female academics’ lower estimated chances to reach full professorship relative to men in LSB (but not NTE). We introduce a novel perceived glass ceiling index (GCI), calculated based on academics’ perceptions of the share of women and men in their direct work environment minus their perceptions of gender ratio among full professors in their field. Results confirm that the perceived glass ceiling is thicker in the non-math-intensive LSB compared to math-intensive NTE fields. Furthermore, only in LSB (but not NTE), women perceived a thicker glass ceiling than men. Moreover, only among female academics, the thicker the perceived glass ceiling, the lower their estimated chances to become full professor one day. Combined, a moderated mediation showed that for women only, a thicker perceived glass ceiling in LSB compared to NTE disciplines predicted their lower estimated chances to advance to full professor level. No such mediation occurred for men. We conclude that women's higher numerical representation in LSB disciplines does not negate a male-dominant normative standard about academic leadership and success. Paradoxically, the perceived odds for female academics to reach the top of their field are lower in fields where they are relatively highly represented, and this may pose unique barriers to women’s perceived opportunities for career success.